Differences between women and men in the relationship between psychosocial stressors at work and work absence due to mental health problem. (28th May 2020) - Gilbert-Ouimet, Mahée; Trudel, Xavier; Aubé, Karine; Ndjaboue, Ruth; Duchaine, Caroline; Blanchette, Caty; Mâsse, Benoît; Vézina, Michel; Milot, Alain; Brisson, Chantal
Abstract : Objectives: Women have a higher incidence of mental health problems compared with men. Psychosocial stressors at work are associated with mental health problems. However, few prospective studies have examined the association between these stressors and objectively measured outcomes of mental health. Moreover, evidence regarding potential differences between women and men in this association is scarce and inconsistent. This study investigates whether psychosocial stressors at work are associated with the 7.5-year incidence of medically certified work absence due to a mental health problem, separately for women and men. Methods: Data from a prospective cohort of white-collar workers in Canada (n=7138; 47.3% women) were used. We performed Cox regression models to examine the prospective association between self-reported psychosocial stressors at work (job strain model) at baseline and the 7.5-year HR of medically certified work absence of ≥5 days due to a mental health problem. Results: During follow-up, 11.9% of participants had a certified work absence, with a twofold higher incidence among women. Women (HR 1.40, 95% CI 1.01 to 1.93) and men (HR 1.41, 95% CI 0.97 to 2.05) exposed to high strain (high demands and low control) had a higher incidence of work absence compared with those unexposed. Among women only, those exposed to an active job situation (high demands and high control) also had a higher risk (HR 1.82, 95% CI 1.29 to 2.56). Conclusions: Prevention efforts aimed at reducing psychosocial stressors at work could help lower the risk of work absence for both women and men. However, important differences between women and men need to be further studied in order to orient these efforts.